Account of Irregularity in the Stress Distribution along Wood and Concrete Sleepers from a Perspective of Granular Media Mechanics. (2017) - Moshenzhal, A.V.
Abstract: The article shows a method aimed at taking into account the irregularity in the distribution of stresses along wooden and reinforced concrete ties transferred to the ballast body. Based on the comparison of the theoretical values of stresses and the values of stresses actually measured in an experimental way, a conclusion has been made as to the viability of the present method implemented on the base of the mechanics of granular media.